Space, liminarity and sociability: ethnography of the dinning room in a hospital unit - Lucas Pereira de Melo; Maria Helena Lenardt (Universidad de Alicante, 2014)
This ethnographic study aimed to interpret the structural and symbolic dimensions of the dinning room through the social interactions between the professionals of the patient team care of a Trauma Unit in an university hospital. Participant observation and semi-structured interviews were used to collect data. The analysis was performed through the development of cultural domains, taxonomic analysis and cultural themes. Four cultural domains were identified: the liminal state and the communitas; the significance of the social interactions outside the dinning room; the meaning of the closed door; and, sharing experiences at the dinning room. The cultural theme was: "the dinning room it is a place that works for everything": space, liminarity, and sociability. We conclude that the existence of physical spaces for sociability between health professionals is essential to conduct the work process, and to the workers' quality of life.